Focus Particles (Just, Even, And, etc.) in the Advertisements - Valančė, Danguolė (Respectus Philologicus, 2015)
The article has been prepared by carrying out the analysis of focus particles: just, even, and, etc. It is important to note that particles play a very important role in linguistic pragmatics: they convey additional meanings called the conventional implicatures, and in that way they strengthen their effect on the consumers. First, the article discusses slogans which were advertised in January – March 2014; then, it discusses how focus particles are used in these slogans, besides the attention which is drawn to the visual advertising and invitation design. The research of advertisements and slogans has approved the prior statement just partially, and for this reason two corpora of advertisement articles (from the fields of education and medicine) were formed. They were analysed separately and later on compared in order to find out whether the focus particles are used similarly in different discourse advertisements. The comparison of the data has disclosed that the focus particles are more commonly used in the original texts related to Lithuania’s education than in the medical advertisements, which are mostly translations used to inform about new medical tools or medical treatment innovations. The research has been carried out by applying the method of corpus linguistics.
Keywords: particle; focused particle; frequency; text of advertising; discourse